The role of portable video camera in surgical education for medical student in an era of Thailand 4.0 - ตุลวรรธนะ, ธวัชชัย (Journal of Medicine and Health Sciences, 2019)
Abstract Video recording of surgical procedure is useful for and education tool for the medical students. The recording system promotes self-directed learning and diminished the learning curve to performing the surgical procedure as well (video-based surgical education). The ideal good features of the video recording system included safety and flexibility use in the operative fields, provides video recordings with the quality of full high definition (1980 x 1080 pixels) to ultra-high definition (4K; 3480 x 2160 pixels) and reasonable prices. The application of portable video recording camera (GoPro Hero5 Black) in surgical education was introduced to the Department of Surgery, Faculty of Medicine, Srinakharinwirot University for intra-operative recorded of 50 surgical procedures. These can promote the small group learning with interactive discussion for the medical students. Furthermore, the recording video files afford the helpful use in academic activity such as; surgical conference or writing the surgical articles. The wireless connection feature of the camera supporting the creation and distribution of the surgical teaching materials, which easy to access and eliminate the inequality in undergraduate surgical education. This educational tool is advantageous for the medical students for the improvement of surgical skills and consistent with the human resource development strategy to become Thailand 4.0 of the government policy. The use of the GoPro camera provided high quality recordings which an excellent tool in surgical education toward the encouragement of self-directed learning and enhance the teaching quality of surgical procedures.